Estrés, ansiedad y depresión en estudiantes de secundaria de una institución educativa privada de Lima durante la pandemia por COVID-19 - Diaz del Olmo Calvo, Francesca (2022)
In the context of COVID-19 pandemic, the aim of his study is to determine the relationship between compulsory social isolation and quarantine with the presence of stress, anxiety and depression in fifth year high school students. It was designed an associative study, by applying the DASS-21 Scale in 66 students, after obtaining informed consent. The results indicated that 80.3 % of the interviewed students had fully complied with compulsory social isolation and quarantine. 24.3 % presented anxiety, 16.7 % stress and 42.3 % depression. Female students obtained higher and significant levels of stress, anxiety and depression in comparison with their male peers; and the students who partially accomplished the social isolation and quarantine due to Covid-19 have higher punctuation in anxiety than those who did not.